Cortical auditory-evoked potentials in children and adults: a comparative study - Jayesh Talekar; C. S. Vanaja (The Egyptian Journal of Otolaryngology, 2025)
Abstract Background Cortical auditory-evoked potentials (CAEPs) measure the electrical activity from the auditory cortex in response to sound. CAEPs are used in clinics for the assessment of benefit from hearing devices such as hearing aids and cochlear implants. It is also used for monitoring the maturation of the auditory cortex. Variability in the acquisition and stimulus parameters used for recording leads to variations in the reported latency, amplitude and morphology of CAEPs. Thus, there is a need to probe more regarding the latency and amplitude of CAEPs in typically developing children.  The present study was designed to compare CAEPs of adults and children in terms of amplitude and latency. Method This study was conducted on 30 adult participants in the age range of 18–30 years and 30 children in the age range of 5 to 8 years. All the participants had hearing sensitivity within normal limits. CAEPs were recorded from Cz referenced to the mastoid and Fz referenced mastoid. Results The amplitude of P1 was significantly greater in children, and there was a reduction in the amplitude and latency values of P1 with age. The occurrence rate of N1, P2 and N2 increased with age. Latency of all the waves decreased with age. Conclusion P1 is the major and consistent peak in children. Age-specific norms are required while using CAEPs in the assessment and rehabilitation of persons with hearing impairment.